Myśl historyczna Diodora Sycylijskiego a recepcja "Biblioteki Historycznej" przez autorów chrześcijańskich - Dudziński, Andrzej (Vox Patrum, 2025)
The article analyses the reasons for the increased popularity of Diodorus Siculus’ Library of History among the early Christian writers. Diodorus’ work is one of the most important literary sources for the ancient history, yet it has been almost entirely ignored by the pagan authors in antiquity. The causes of the unexpected interest on the part of the Christian authors is thereby even more intriguing. Firstly, the article discusses briefly the early reception of Diodorus’ work by both the pagan and the Christian writers, up to the byzantine period. Next it discusses the philosophical approach of euhemerism. Diodorus’ decision to embrace the euhemeristic philosophy is usually considered the main reason for the popularity of the Library among the Christian authors, who used it to demonstrate the falsehood of the pagan gods. Notwithstanding the importance of euhemerism, the article points out other aspects of the Diodorus’ work that the Christian authors may have found appealing. These include first and foremost the linear (as opposed to circular) conception of time adopted by Diodorus, his interest in providing his readers with the moral lessons, and his decision to bring all the peoples of the oikoumene into one historical narrative. The article puts forward a hypothesis that Diodorus’ conviction that the history and historians, almost like the priests of the “divine providence”, support the development of the humanity, may also have been attractive to the Christian writers.